The Arts of Cinema - Seel, Martin (Book collections on Project MUSE., 2018)
"Explores film's connections to the other arts and the qualities that distinguish it from them. He explores the cinema's singular aesthetic potential and uses specific examples from a diverse range of films--from Antonioni and Hitchcock to The Searchers and The Bourne Supremacy--to demonstrate the many ways this potential can be realized"--